The development of oh my tajweed learning mobile application / Muhammad Taufiq Zolkeflee - Zolkeflee, Muhammad Taufiq (2015)
Tajweed is the rule to recite the Quran which is how to read the arabic word and how to pronounce it in the correct way. If the Quran recite without tajweed, it can change the meaning of the word and phrase in the Quran. So, it is a must as a muslim to learn and understand the rule of tajweed before recite the Quran. To learn about tajweed, most children have a difficulty to learn tajweed due to less learning time to learn tajweed. The growing technology of mobile devices encourages the developement of learning-based mobile application or M-learning. M-learning are becoming popular nowadays becuse it can be learn at any time and at any places. This can help children to learn tajweed without consider tomuch time than attending tajweed learning class. Therefore, this project is about developing Oh My Tajweed Learning mobile application. The objective is to identify requirements, design and develop a mobile application in learning tajweed. Users can learn from the tutorial about tajweed topics in the application. The method used in getting the requirements was by interviewing a tajweed teacher, Norhafiza Binti Ahmad at "Sekolah Kebangsaan Rendah Agama Seksyen 3 Shah Alam" and conduct interview with children age 6 to 12 years old at Puncak Alam area. The development tool used in developing the application is using Adobe Flash CS6. Mobile Application Developement Life Cyle also known as MADLC was used as the methodology in developement this application, because of its systematic approach in developing mobile applications. In research and findings, the functional requirement, non-functional requirement, use case, use case description, work system, data flow diagram, entity relationship diagram and storyboard of the application were constructed. Future works that should be added to enhance the application is by adding more tajweed topics, use another mobile platform such as IOS -based platform and include more language in the application.